2007
DOI: 10.1080/01926230701460000
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Neuroendocrine Cell Hyperplasia: Identification, Diagnostic Criteria and Incidence in Untreated Ageing Rats of Different Strains

Abstract: Pulmonary Neuroendocrine Cells (PNEC) are found as clusters called neuroepithelial bodies (NEB) or as single cells scattered in the respiratory epithelium. Pulmonary neuroendocrine cell hyperplasia is recorded in humans and experimentally manipulated rodents. The objectives of this work were to identify the optimal immunohistochemical markers for PNEC in the rat for use on paraffin-embedded, formalin-fixed material and to provide the first comparative incidence of PNEC hyperplasia in untreated 2-year-old rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…5). Importantly, we demonstrated that the majority of ENK-IR cells coexpressed DOR or CgA, a marker for neuroendocrine structures [18,19], indicating that solitary PNECs within bronchial epithelium coexpressed both DOR and its ligand ENK (Fig. 6A-H).…”
Section: Coexpression Of Penk Enk Processing Enzymes and Dor In Nementioning
confidence: 86%
See 1 more Smart Citation
“…5). Importantly, we demonstrated that the majority of ENK-IR cells coexpressed DOR or CgA, a marker for neuroendocrine structures [18,19], indicating that solitary PNECs within bronchial epithelium coexpressed both DOR and its ligand ENK (Fig. 6A-H).…”
Section: Coexpression Of Penk Enk Processing Enzymes and Dor In Nementioning
confidence: 86%
“…Our findings showed colocalization of PENK with ENK and its processing enzymes within PNECs. By use of CgA, a specific marker for neuroendocrine cells, we could clearly differentiate PNECs from other cells of the bronchial epithelium [18,19]. PNECs are part of the diffuse neuroendocrine system within the bronchial epithelium, display endocrine and paracrine secretory mechanisms, and are associated with a dense network of sensory nerve fibers (see review of Nagaki et al [34]).…”
Section: Discussionmentioning
confidence: 97%
“…In neuroendocrine cells of the larynx and trachea, serotonin could not be demonstrated, whereas in the lung, serotonin-containing cells were seen. (Adriaensen et al 2001;Boorman, Morgan, and Uraih 1990;Dungworth, Ernst, et al 1992;Dungworth et al 2001;Elizegi et al 2001;Gopinath, Prentice, and Lewis 1987;Haworth et al 2007;Karube et al 1989;Kasacka and Sawicki 2004;Kerns et al 1983;Larson et al 2004;Lauweryns and Van Ranst 1988;Lauweryns et al 1987;D. Lewis 1991;Luts et al 1991;Maronpot et al 1986;McBride et al 1990;Montuenga et al 1992;Pack, Al-Ugaily, and Morris 1981;Rehm and Kelloff 1991;Shimosegawa and Said 1991;Takahashi, Iwasaki, and Ide 1985;Van Lommel 2001;Van Lommel et al 1999) Hyperplasia with Cellular Atypia (Dysplasia): Larynx, Trachea, Bronchi, Bronchioles Pathogenesis/cell of origin: Proliferation of respiratory epithelium, or submucosal glands.…”
Section: Larynx Trachea Bronchi and Bronchiolesmentioning
confidence: 96%
“…Diagnosis of a malignant tumor is based on one or more features including overall size, loss of polarity of epithelium, a high degree of atypia, increased numbers of mitoses, or invasive behavior. (Haworth et al 2007;Kasacka and Sawicki 2004;Levasseur et al 2004;Reznik, Stinson, and Ward 1980;Reznik-Schüller 1983a, 1983bRouquier and Giorgi 2007;Schüller, Gregg, and Reznik 1990;Shimosegawa and Said 1991;Trinh and Storm 2004) Hyperplasia with Atypia ( Figure 40): Nasal Cavity, Nasopharynx, Paranasal Sinus Pathogenesis/cell of origin: Hyperplastic squamous, respiratory, olfactory, or glandular epithelium. Diagnostic features:…”
Section: Inflammation Acute (Figures 4 and 20): Nasal Cavitymentioning
confidence: 97%
“…The presence of clusters of neuroendocrine cells within the respiratory or olfactory epithelium of the nasal cavity and within the lungs may be observed (Haworth et al 2007). …”
Section: Background Lesions Of the Upper Respiratory Tractmentioning
confidence: 99%